Identification of a New de Novo Mutation Underlying Regressive Episodic Ataxia Type I - Karalok, Zeynep S.; Megaro, Alfredo; Cenciarini, Marta; Guven, Alev; Hasan, Sonia M.; Taskin, Birce D.; Imbrici, Paola; Ceylaner, Serdar; Pessia, Mauro; D'Adamo, Maria C. (Frontiers in Neurology, 2018)
Episodic ataxia type 1 (EA1), a Shaker-like K+channelopathy, is a consequence of genetic anomalies in the KCNA1 gene that lead to dysfunctions in the voltage-gated K+ channel Kv1. 1. Generally, KCNA1 mutations are inherited in an autosomal dominant manner. Here we report the clinical phenotype of an EA1 patient characterized by ataxia attacks that decrease in frequency with age, and eventually leading to therapy discontinuation. A new de novo mutation (c.932G>A) that changed a highly conserved glycine residue into an aspartate (p.G311D) was identified by using targeted next-generation sequencing. The conserved glycine is located in the S4–S5 linker, a crucial domain controlling Kv1.1 channel gating. In silico analyses predicted the mutation deleterious. Heterologous expression of the mutant (Kv1.1-G311D) channels resulted in remarkably decreased amplitudes of measured current, confirming the identified variant is pathogenic. Collectively, these findings corroborate the notion that EA1 also results from de novo variants and point out that regardless of the mutation-induced deleterious loss of Kv1.1 channel function the ataxia phenotype may improve spontaneously.